2015
DOI: 10.4314/gmj.v49i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of the prevalence of <i>Helicobacter pylori</i> among patients at a corporate hospital in Ghana

Abstract: SUMMARY Introduction:Helicobacter pylori (H. pylori) discovered in 1982, has strongly been associated with multiple clinical disorders of the gastrointestinal tract. This study described the prevalence of H. pylori among large numbers of patients over two different time periods in Accra, Ghana. Methods: It was a retrospective records review on patients attending a quasi-government hospital in Accra, Ghana, during two time periods, 1999 and 2012. A total of 2401 records were reviewed, 1128 in first period and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…This reduction can be explained by the improvement in hygiene conditions which minimizes transmission, better therapeutic management of the patients, and the unintentional eradication of the bacteria by the increased use of antibiotics for the treatment of other infections. Similar decreases in the prevalence of H. pylori infection have been observed in several developing countries: In Ghana, it decreased from 69.7% in 1999 to 45.2% in 2012 . A Brazilian study reported a 5.2% decrease in prevalence between 2004 and 2014 .…”
Section: Discussionsupporting
confidence: 69%
“…This reduction can be explained by the improvement in hygiene conditions which minimizes transmission, better therapeutic management of the patients, and the unintentional eradication of the bacteria by the increased use of antibiotics for the treatment of other infections. Similar decreases in the prevalence of H. pylori infection have been observed in several developing countries: In Ghana, it decreased from 69.7% in 1999 to 45.2% in 2012 . A Brazilian study reported a 5.2% decrease in prevalence between 2004 and 2014 .…”
Section: Discussionsupporting
confidence: 69%
“…Educational level has been known as an important determinant of H. pylori prevalence in both developed and developing countries [28]. In the current study, illiteracy of mothers was significantly associated with positive H. pylori infection; this could be explained by the assumption that the mothers' educational status reflects on the healthy habits and hygienic behavior acquired by their children.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies in Korle Bu Teaching Hospital reported an incidence of 75 % [3, 4]. However, a recent publication also reports an H. pylori prevalence of 69.7 % (1999) and 45.2 % (2012) in Accra [12]. This suggests a change in H. pylori prevalence with time.…”
Section: Discussionmentioning
confidence: 98%
“…In addition the vast majority of our study subjects were from urban areas where the standard of living is higher. However, the frequent use of antibiotics may also contribute to the relatively low prevalence being reported recently [12]. Also the recent use of PPI’s may contribute to the low prevalence.…”
Section: Discussionmentioning
confidence: 99%